ORGANIZATIONAL CULTURE AND NURSES’ BEHAVIOUR IN IMPLEMENTING PATIENT SAFETY - Santa Monika Sinurat; Septiani Simanullang; Solagratia Latumaerissa; Riama Marlyn Sihombing; Windy Sapta Handayani Zega (Universitas Pelita Harapan, 2023)
Patient safety is an essential indicator of healthcare quality. The initial interview indicated that within a month, there is always a patient safety incident such as patient falls and medication errors. The organizational culture, vision, mission, goals, and leadership style surely have an impact on a nurse's behaviour when it comes to patient safety. Many research studies discovered that the culture of organization inherent in nurses impacts the quality of hospital services, and nurses can reflect themselves as professional nurses with the organizational performance culture. This study aimed to find a correlation between corporate culture and nurse’s behaviour to patient safety. This study used a quantitative correlational method with a cross-sectional approach. The sample consisted of 191 nurses who had been selected through accidental sampling. The questionnaires on organizational culture and nurse’s behaviour in patient safety are distributed online via Google Forms and have been tested for its validity and reliability on 31 nurses. This study was conducted from March 29 to June 30, 2020. More than half of the respondents observed a bad organizational culture, and more than half of the nurses demonstrated poor behaviour in implementing patient safety. The Spearman correlation test revealed no significant relationship between corporate culture and nurse’s behaviour in adopting patient safety. The hospital administration can provide coaching in terms of socialization, training, mentorship, and supervision through the head nurse or team leader.